Instructional Progression and the Role of Working Models in Physical Education - DERVENT, FATİH (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
Given that the primary task of teaching is to teach the content of physical education, attention to how instructional tasks operationalize the curriculum and progress learning is essential knowledge for teachers. Task progression in physical education occurs when tasks are designed to successively and incrementally present physical education content to students, leading to more sophisticated knowledge and improvement in performance and knowledge. We present a synthesis of the literature on instructional tasks, content knowledge, and content development and use this synthesis to examine the concept of working models as a tool to aid teaching in physical education. We present four propositions to guide thinking about working models and conclude with implications for student learning, teachers, teacher educators and researchers.
Keywords: Content knowledge; instructional tasks; content development; pedagogical content knowledge; PEDAGOGICAL CONTENT KNOWLEDGE; COMMON CONTENT KNOWLEDGE; HEALTH-RELATED FITNESS; CONTENT MAPS; TEACHERS; STUDENTS; VALIDATION; SKILLS; SPORT; TASKS